Effects of chitosan combined with microbes on blue mold of apples - Fu, Ruimin; Yu, Feng; Zhang, Hong; Liu, Chunlei; Chang, Huiping; Chen, Wuling (Bangladesh Journal of Botany, 2024)
Investigation on the inhibitory effect of chitosan combined with antagonistic bacteria on pathogenic fungi, at different concentrations on Penicillium expansum were studied in vitro and in vivo with Japanese Red Fuji apples. The chitosan solution with the concentration of 2% had the strongest resistance to Penicillium expansum and blue mold decay without affecting the growth of Bacillus amyloliquefaciens BA-16-8. Both the bacterial suspension and cell-free fermentation liquor of Bacillus amyloliquefaciens BA-16-8 could inhibit Penicillium expansum, and the former is superior to the latter in effect. Bacillus amyloliquefaciens BA-16-8 combined with chitosan can inhibit the activity and toxin-producing ability of Penicillium expansum. Bangladesh J. Bot. 53(1): 25-32, 2024 (March)